PET of Poly (ADP-Ribose) Polymerase Activity in Cancer: Preclinical Assessment and First In-Human Studies - Loren S. Michel; Samantha Dyroff; Frank J. Brooks; Katherine J. Spayd; Sora Lim; Jacquelyn T. Engle; Sharon Phillips; Benjamin Tan; Andrea Wang‐Gillam; Christopher Bognar; Wenhua Chu; Dong Zhou; et al. (2016)
Purpose To demonstrate that positron emission tomography (PET) with fluorine 18 (18F) fluorthanatrace (FTT) depicts activated poly (adenosine diphosphate–ribose)polymerase (PARP) expression and is feasible for clinical trial evaluation. Materials and Methods All studies were conducted prospectively from February 2012 through July 2015 under protocols approved by the local animal studies committee and institutional review board. The area under the receiver operating characteristic curve (AUC, in g/mL· min) for 18F-FTT was assessed in normal mouse organs before and after treatment with olaparib (n = 14), a PARP inhibitor, or iniparib (n = 11), which has no PARP inhibitory activity. Murine biodistribution studies were performed to support human translational studies. Eight human subjects with cancer and eight healthy volunteers underwent imaging to verify the human radiation dosimetry of 18F-FTT. The Wilcoxon signed rank test was used to assess for differences among treatment groups for the mouse studies. Results In mice, olaparib, but not iniparib, significantly reduced the 18F-FTT AUC in the spine (median difference before and after treatment and interquartile range [IQR]: −17 g/mL· min and 10 g/mL · min, respectively [P = .0001], for olaparib and −3 g/mL · min and 13 g/mL · min [P = .70] for iniparib) and in nodes (median difference and interquartile range [IQR] before and after treatment: −23 g/mL · min and 13 g/mL · min [P = .0001] for olaparib; −9 g/mL · min and 17 g/mL · min [P = .05] for iniparib). The effective dose was estimated at 6.9 mSv for a 370-MBq 18F-FTT dose in humans. In humans, the organs with the highest uptake on images were the spleen and pancreas. Among five subjects with measurable tumors, increased 18F-FTT uptake was seen in one subject with pancreatic adenocarcinoma and another with liver cancer. Conclusion The results suggest that 18F-FTT uptake reflects PARP expression and that its radiation dosimetry profile is compatible with those of agents currently in clinical use. © RSNA, 2016 Online supplemental material is available for this article.